Association between physical activity, fiber and salt intake with hypertension in adolescents with obesity - Ni Luh Putu Sudiasih; Dewa Nyoman Wirawan; I Gusti Lanang Sidiartha (Public Health and Preventive Medicine Archive, 2019)
Background and purpose: There are indications that the prevalence of obesity among adolescents is increasing which is one of the main factors of hypertension. This study aims to determine the association between hypertension among obese adolescents with physical activity, fiber and salt intake. Methods: This study used a cross-sectional design among obese adolescents aged 12-15 years. The study was conducted at six public/ private middle schools in the North Denpasar Sub-district, Denpasar City, Bali Province. The samples of 203 children were selected from the results of obesity screening conducted by North Denpasar III Public Health Center (PHC). Data collection was conducted over July-September 2018 with data included social demographics, body weight and height, blood pressure, consumption frequency of vegetables, fruits and high salt content foods, and physical activity carried out in the past week. Data analysis with logistic regression was conducted to determine the association between physical activity, fiber and salt intake with hypertension among obeseadolescents. Results: This study found that of 203 respondents, 14.8% had hypertension. Multivariate analysis showed that hypertension in obese adolescents was associated with salt intake ≥1500 mg/day with adjusted odd ratio (AOR) of 5.19 (95%CI: 2.20-12.22), inadequate physical activity (AOR=5.87; 95%CI: 1.19-29.00) and inadequate fiber intake (AOR=2.43; 95%CI: 0.27-21.76). Conclusion: Salt intake ≥1500 mg/day and inadequate physical activity are associated with hypertension among obese adolescents. A reduction in the consumption of processed foods that are high in salt and increasing physical activity would improve adolescent health.